Designing High Water Resistance Woodplastic Composites From Steam Exploded Fiber And High-Density Polyethylene. - Mat Taib, Dr. Razaina; Mohd. Ishak, Prof. Zainal Arifin; Hj. Din, Prof. Rozman (Universiti Sains Malaysia, 2007)

(untitled)
Composites of high-density polyethylene and acetylated steam-exploded Acacia mangium fibers (AAEF) were prepare using a heated 2 roll-mill, compression molded and tested for tensile properties.